THE IMPORTANCE OF ACHIEVING LOCAL CONTROL IN PATIENTS WITH SQUAMOUS CELL HEAD AND NECK CANCER - T. M. Sharabura; A. V. Vazhenin; A. O. Guz; A. S. Zakharov; A. A. Lozhkov; O. N. Davydova; M. M. Pimenova; М. А. Zbitskaya (Сибирский онкологический журнал, 2017)
The achievement of local control in patients presenting with locally advanced squamous cell head and neck carcinoma is of great importance. Postoperative radiotherapy with concurrent chemotherapy was shown to improve the outcome of surgery, but was also associated with higher rates of acute toxicity. Analysis of the  results depending on risk factors (rT3-4, N+ , extracapsular extension, vascular and perineural invasion, positive  resection margin) allowed for identification of highand intermediate-risk patients with the greatest benefit from more aggressive treatment. Selectively delivering total doses of radiotherapy, in particular 3-D conformal and intensity modulated radiotherapy is another way to more effective and less toxic treatment. The results of combined modality treatment with postoperative radiotherapy were presented for 74 patients with stage III–IVA squamous cell head and neck carcinoma. The problem of achieving local control was analyzed with the assessment of risk factors for differential delivery of the total doses. The optimization of postoperative radiation therapy in terms of volume and dose was based on the identification of different clinical risk factors, which in turn is possible with a multidisciplinary approach involving a surgeon, pathologist, radiologist, radiotherapist and medical physicist.